DESIGN PROCESS OF DME STORAGE SYSTEM AS ASSEMBLY PARTS OR MAINTENANCE SPARE PARTS INVENTORY IN OFFSHORE OIL DRILLING PIPING SYSTEM - Sally Cahyati; Daniel Rizky Mahendra (Universitas Mercu Buana, 2021)
Discharge Manifold Equipment (DME) is an output pipe from a pump that bears an essential role in a piping system in offshore oil drilling, so it is a must to assure good bears condition whenever used. It is not an easy thing because DME is a significant and heavy component. Also, unfavourable conditions of offshore climate can accelerate its corrosion. Storage with the modular rack uses an offshore container certified DNV 2.7-1 / EN 12079 will be designed to fulfil those needs. The storage has an important role as an element in inventory, both the storage system for assembly parts or maintenance spare parts. This storage will be design using 4 (four) phases from VDI 2221 methods, namely; task clarification, conceptual design, embodiment design, and detailed design. Hydraulic power will be added to the system to support the piston movement so that the storage rack can be moved automatically by the hydraulic system. This storage has given the best solution for a systematic storing DME in the piping system of offshore oil drilling.